A Case Report of Hyperestrogenism in Prader-Willi Syndrome - Isabella Albanese, MDCM, MS; Natasha Garfield, MDCM (AACE Clinical Case Reports, 2022)
Objective: Prader-Willi syndrome (PWS) is associated with multiple endocrinopathies, including hypogonadism. The mechanism underlying hypogonadism in PWS is thought to be secondary to hypothalamic dysfunction, primary gonadal defect, or a combination of both. Here, we present a case of hyperestrogenism in PWS due to concomitant polycystic ovary syndrome (PCOS) and therapeutic considerations regarding hormone replacement therapy (HRT). Case Report: An 18-year-old woman with PWS transferred to adult care from pediatrics was found to have hyperestrogenism (specifically, elevated estrone with normal estradiol levels). Additionally, she demonstrated oligomenorrhea and hyperandrogenism, meeting diagnostic criteria for PCOS. After 3 months of therapy with cyclic medroxyprogesterone alone, she developed normal withdrawal bleeding. Discussion: Given the elevated estrone and normal estradiol levels, our patient’s hyperestrogenism is thought to be a direct result of her hyperandrogenism due to peripheral conversion. Prolonged exposure to unopposed estrogen is an established risk factor for endometrial cancer development in PCOS; thus, this was taken into account regarding her HRT, and she was treated with cyclic progesterone alone. Conclusion: Women with PWS are typically treated with combined estrogen and progesterone HRT; however, our case, a unique presentation of PCOS in PWS, demonstrated the importance of tailoring HRT to a patient’s specific needs.